Perubahan Sosial Berbasis Tasawuf: Studi Kasus Fethullah Gülen Dan Gülen Movement - Sulaiman Sulaiman (AL-TAHRIR, 2016)
Abstract: This article aims at analyzing Fethullah Gülen and the Gülen Movement which have succeeded in performing social change based on the teaching of Sufism. He did Sufism creativity in order that Sufism teaching was able to respond the changes that occur in the modernlife. He believed that, only by reinterpretation and contextualization of Sufism, the spiritual dimension of Islam would be able to perform the transformation or social change among the Muslims. Therefore, by using Max Weber’s theory of social action, this paper will analyze three key teachings of Sufism of Gülen: ascetic (zuhd), inbisat (expansion), and hizmet. Based on the Weber's theory, Gülen occupied a very central and authoritative position: agent/actor, action and meaning. As a source of meaning and interpreter of meaning, the key concepts of Sufism were transformed by Gülen to the internal and external communities so that they had made a move to do social movements and humanity. For the followers of Gülen, the movement was called the Gülen Movement or the Hizmet Movement which was engaged in the fields of education, health care, humanitarian assistance, and the mass media. All forms of movement were entirely based on the spiritual values of Islam that had been formulated by Gülen. الملخص: يهدف هذا البحث إلى تحليل شخصية فتح الله غولن وحركته الذي تمكن من القيام بالتغيير الاجتماعي على أساس التعاليم الصوفية. إن فتح الله غولن قام بإحياء التصوف في صورته الجدّية والحيوية في حياة الإنسان المعاصر. ويعتقد أن إعادة التفسير لتعاليم التصوف مع مراعاة الواقع قادرة على التغيير الاجتماعي بين المسلمين. من أجل ذلك، أن استخدام نظرية ويبر، يمكن تحليل تعاليم التصوف الثلاثة التي اعتمد عليها فتح الله غولين، وهي : الزهد، إينبيسات (التوسع)، والخدمة. بهذه النظرية، يحتل غولن منصبا استراتيجيا وموثوقا: كالممثل والعمل، والمعنى.وأنه مصدر للمعنى والمفسر له، وبهذا المفهوم، نقله غولن  إلى المجتمع الداخلي والخارجي  للقيام بالحركات الاجتماعية والإنسانية . ويطلق أتباع غولن هذه الحركة باسم حركة غولن أو حركة الخدمة التي تشارك في التعليم والرعاية الصحية والمساعدة الصحية ووسائل الإعلام. يُنفّذ جميع هذه الأنشطة على أساس القيم الروحية التي صاغها غولن إلى أتباعه .  Abstrak: Artikel ini bertujuan untuk menganalisis Fethullah Gülen dan Gerakan Gülen yang berhasil melakukan perubahan sosial berdasarkan ajaran tasawuf. Ia melakukan sufism creativity (kreativitas sufisme) yang bertujuan agar ajaran tasawuf mampu merespon perubahan-perubahan yang terjadi dalam kehidupan manusia modern. Ia meyakini bahwa hanya dengan reinterpretasi dan kontekstualisasi ajaran tasawuf, maka dimensi spiritualitas Islam ini akan mampu melakukan transformasi atau perubahan sosial di kalangan umat Islam. Karena itu, dengan menggunakan teori tindakan sosial Weber, tulisan ini akan menganalisis tiga ajaran kunci tasawuf Gülen: zuhud, inbisat (ekspansi), dan hizmet. Dengan kerangka teori Weber, maka Gülen menempati posisi yang sangat sentral dan otoritatif: agen/aktor, aksi, dan makna. Sebagai sumber makna dan penafsir makna, maka konsep kunci tasawuf tersebut ditransformasikan oleh Gülen ke komunitas internal dan eksternal sehingga mereka tergerak untuk melakukan gerakan-gerakan sosial dan kemanusiaan. Bagi para pengikut Gülen, gerakan itu menamakan dirinya Gerakan Gülen atau Gerakan Hizmet yang bergerak dalam bidang pendidikan, layanan kesehatan, bantuan-bantuan kemanusiaan, dan media massa. Semua bentuk gerakan ini sepenuhnya didasari oleh nilai-nilai spiritualitas Islam yang telah diformulasikan oleh Gülen.